2016
DOI: 10.1371/journal.pone.0148484
|View full text |Cite
|
Sign up to set email alerts
|

The Histaminergic Tuberomamillary Nucleus Is Involved in Appetite for Sex, Water and Amphetamine

Abstract: The histaminergic system is one component of the ascending arousal system which is involved in wakefulness, neuroendocrine control, cognition, psychiatric disorders and motivation. During the appetitive phase of motivated behaviors the arousal state rises to an optimal level, thus giving proper intensity to the behavior. Previous studies have demonstrated that the histaminergic neurons show an earlier activation during the appetitive phase of feeding, compared to other ascending arousal system nuclei, parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Good memory consolidation of fear tasks requires emotional arousal and the engagement of the basolateral amygdala (BLA) ( Izquierdo et al, 2016 ). Emotionally relevant experiences activate the histaminergic system ( Contreras et al, 2016 ) that is crucial for the consolidation, retrieval, and extinction of such memories with different anatomical and temporal patterns ( Fiorenza et al, 2012 ; Benetti et al, 2015 ; Fabbri et al, 2016 ). In particular, activation of histamine H 1 or H 2 receptors in the BLA (but also in the hippocampus, infralimbic, and ventromedial prefrontal corteces) facilitates memory consolidation of inhibitory avoidance and contextual fear conditioning, whereas their specific antagonists have an opposite effect in the consolidation of different tasks ( Cangioli et al, 2002 ; Giovannini et al, 2003; Silva et al, 2006 ; Benetti and Izquierdo 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Good memory consolidation of fear tasks requires emotional arousal and the engagement of the basolateral amygdala (BLA) ( Izquierdo et al, 2016 ). Emotionally relevant experiences activate the histaminergic system ( Contreras et al, 2016 ) that is crucial for the consolidation, retrieval, and extinction of such memories with different anatomical and temporal patterns ( Fiorenza et al, 2012 ; Benetti et al, 2015 ; Fabbri et al, 2016 ). In particular, activation of histamine H 1 or H 2 receptors in the BLA (but also in the hippocampus, infralimbic, and ventromedial prefrontal corteces) facilitates memory consolidation of inhibitory avoidance and contextual fear conditioning, whereas their specific antagonists have an opposite effect in the consolidation of different tasks ( Cangioli et al, 2002 ; Giovannini et al, 2003; Silva et al, 2006 ; Benetti and Izquierdo 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…The brain histaminergic system is likely involved in emotionally ‘appetitive’ behaviours as well. The histaminergic system is important for appetitive behaviour related to feeding (Valdés et al, 2010) and other goal‐directed behaviours, as observed in rats motivated to obtain sex, amphetamine or drinking water (Contreras et al, 2016). The authors suggested that histamine critically contributes to the intensity component of several appetitive behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine in the brain accumulates in mast cells, astrocytes ( 23 ), and in the few histaminergic neurons that are concentrated in the hypothalamus from which they project to most of the brain areas including the hippocampus and cortex ( 24 ). Neuronal histamine is implicated in memory, control of the sleep/wake cycle, feeding, thermoregulation, motility, and it is considered an endogenous neuroprotective mediator against excitotoxicity ( 25 , 26 ). Histamine in the brain is mainly degraded by N -methyl transferase producing N -methylhistamine ( 27 ) which is, in turn, a good substrate for MAO-B.…”
Section: T1am Pharmacokineticmentioning
confidence: 99%